ANALISIS SOAL TES BERPIKIR KRITIS TIPE HOTS BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT DI SEKOLAH DASAR - Neneng Widya Sopa Marwa; Ghullam Hamdu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose in this study is to know the quality of the problem of PAT IPA SD Grade 5 in Tasikmalaya city and to know the extent to which the question can measure students' critical thinking skills in high-level thinking (HOTS) and in the context of ESD(Education for Sustainable Development) which is the demand of the current Curriculum 2013 and the needs of the world today. This study uses qualitative methods using descriptive approaches. The research design used is content analysis. The population in this study is the whole problem of PAT IPA SD Grade 5 in Tasikmalaya city which amounts to 10 subdistricts. Sampling in this study using Simple Random Sampling technique, so that obtained samples in the form of 100 PAT IPA elementary school questions from 5 subdistricts in tasikmalaya city. Data collection is conducted through interviews and documentation studies. While the technical analysis of data in this study uses descriptive statistics and instruments in this study using analysis sheets and assessment rubrics. The results showed that half of the pat ipa problems of GRADE 5 elementary school in Tasikmalaya city are HOTS type (43%) and the other half are lots (57%). Furthermore, the characteristics of esd-based critical thinking test questions contained in pat questions are small (14.3%) contains indicators on the importance of self-contribution in sustainability life, half of which (57.1%) contains about how to interpret the phenomenon to the impact of sustainable living and less than half (28.6%) contains indicators that describe messages and impressions related to sustainable living.